Ibn Sina: philosopher and scientist of Islam - T.P., Sageerali (Penerbit Universiti Kebangsaan Malaysia, 2025)
Ibn Sina is one of the greatest scholars in world history. He was a brilliant philosopher who synthesized Islamic theology with Aristotelian thought. His most famous philosophical work is ‘The Book of Healing’, a vast encyclopedia that covers logic, physics, mathematics, and metaphysics. He also wrote extensively on Ethics, Psychology, and Metaphysics. His work had a profound influence on the development of Western thought. His ideas were studied by philosophers and scientists for centuries. And he is also known as Ibn Sina in the West, and he has developed many science fields, such as Medicine, Astronomy, Mathematics, Philosophy and psychology and classified hundreds of books in different sciences. His most famous scientific work is The Canon of Medicine, a medical encyclopedia that remained a standard medical text in both the Islamic world and Europe for centuries. The Canon covers a wide range of topics, including anatomy, physiology, pathology, pharmacology and surgery. The methodology of this study adopts a qualitative and historical approach to explore the life, contributions and intellectual legacy of Ibn Sina as a philosopher and scientist. The research involves a comprehensive textual analysis of Ibn Sina’s major works, including The Book of Healing and The Canon of Medicine, focusing on his contributions to logic, metaphysics, ethics, psychology and medicine. A comparative study is conducted to examine how Ibn Sina synthesized and expanded upon the works of predecessors such as Aristotle, al-Kindi and al-Farabi, highlighting his unique integration of Islamic theology with Greek philosophy. The study also contextualizes Ibn Sina’s work within the socio-political and cultural framework of the Islamic Golden Age, exploring the influence of the Samanid Empire and the religious and political dynamics of his time.